Unemployment crisis among fresh graduates / Nor Azilah Husin … [et al.] - Nor Azilah Husin, Nor Azilah Husin; Rasli, Salina; Ganesh Kumar, Murugan Shri; Suppiah, Ganeswary (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
The phenomenon of graduate unemployment has culminated many policy implications for higher education in many developed nations, such as Malaysia. The unemployment rate among fresh graduates increased to 25% in 2020 compared to 13.8% the year before, resulting in the total unemployment of new graduates a whopping 116,161 people. Why such an alarming rate? This paper aims to examine factors influencing unemployment crisis among fresh graduates. The obtained data on employers' preference, candidate attributes, and economic instability was done through a survey questionnaire distributed among 130 fresh graduates. Both descriptive analyses on demographic characteristics and inferential statistics were applied to analyse the data. The findings indicate significant association between employer's preference, candidate attributes, and economic instability with the unemployment crisis. The findings shed light on measures to be taken by the education ministry to prepare fresh graduates for better employment prospects. A revision to the higher education academic curriculum is recommended to meet the job market's and stakeholders' needs for better graduate employability.